2015
DOI: 10.18616/is.v4i2.2233.32-44
|View full text |Cite
|
Sign up to set email alerts
|

Promoção à saúde bucal de crianças internadas em um hospital infantil de alta complexidade de um município do sul catarinense

Abstract: ResumoObjetivo: Investigar as condições de saúde e higiene bucal em crianças internadas em um hospital infantil de alta complexidade localizado num município do Sul Catarinense. Métodos: Estudo transversal, descritivo e de abordagem quantitativa, realizado no Hospital Materno Infantil Santa Catarina, do município de Criciúma-SC, com uma amostra de 80 crianças. Foram coletados dados sociodemográficos das mães das crianças, motivo de internação, aleitamento materno, uso de chupetas ou mamadeira, hábito de adoçar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 2 publications
0
6
0
7
Order By: Relevance
“…As much as 17 (60.7%) [3][4][5][6][7]10,18,19,[21][22][23][26][27]29,33 studies were published between 2014 and 2017, 4 (14.3%) 2,16,30,32 in 2011, 3 (10.7%) 24,25,28 in 2010, 2 (7.1%) 17,20 in 2013, and 1 (3.6%) in 2008 and 1 in 2012. 15,31 Most of the studies were conducted in São Paulo state, with 7 (25%) 2,15,17,19,22,24,26 publications, followed by the states of Santa Catarina (n=4, 14.3%), 7,25,28,32 Paraná (n=3, 10.7%) 6,13,30 and Mato Grosso (n=2, 5.6%). 18,23 The states of Bahia, Goiás, Mato Grosso do Sul, Minas Gerais, Pará, Paraíba, Pernambuco, Piauí, Rio Grande do Norte and Rio Grande do Sul had 1 (2.8%) publication each, accounting to 28% of the sample.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As much as 17 (60.7%) [3][4][5][6][7]10,18,19,[21][22][23][26][27]29,33 studies were published between 2014 and 2017, 4 (14.3%) 2,16,30,32 in 2011, 3 (10.7%) 24,25,28 in 2010, 2 (7.1%) 17,20 in 2013, and 1 (3.6%) in 2008 and 1 in 2012. 15,31 Most of the studies were conducted in São Paulo state, with 7 (25%) 2,15,17,19,22,24,26 publications, followed by the states of Santa Catarina (n=4, 14.3%), 7,25,28,32 Paraná (n=3, 10.7%) 6,13,30 and Mato Grosso (n=2, 5.6%). 18,23 The states of Bahia, Goiás, Mato Grosso do Sul, Minas Gerais, Pará, Paraíba, Pernambuco, Piauí, Rio Grande do Norte and Rio Grande do Sul had 1 (2.8%) publication each, accounting to 28% of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify the scenario of hospital dentistry in Brazil through published studies, it was found that 6 (21.4%) [13][14][15]17,23,26 studies had a control group; 17 (60.7%) [4][5][6]16,18,19,[20][21][22]24,[27][28][29][30][31][32][33] were related to patients' oral health profile and 5 (17.9%) 2,3,7,10,25 were questionnaire-based studies of which 4 3,7,10 involved only patients and 1 25 involved patients, caregivers and healthcare professionals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations